2016
DOI: 10.1007/s00421-016-3522-8
|View full text |Cite
|
Sign up to set email alerts
|

No influence of ischemic preconditioning on running economy

Abstract: The properties of ischemic preconditioning thought to affect exercise performance at vigorous to severe exercise intensities, which generate more extensive physiological challenge, are ineffective at submaximal workloads and, therefore, do not change running economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
0
16
1
1
Order By: Relevance
“…Thus, the changes reported herein are feasible and most likely reflect the training status of the participants recruited. Our findings contrast those reported after acute application of IPC, where no changes in running economy (Kaur et al 2017) or cycling economy (Clevidence et al 2012;Kilding et al 2018) have been reported. Furthermore, increasing the number of ischemic episodes during an acute application (up to 8 x 5-min), beyond the traditional 4 x 5-min protocol, elicited no additional improvements in performance (Cocking et al 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the changes reported herein are feasible and most likely reflect the training status of the participants recruited. Our findings contrast those reported after acute application of IPC, where no changes in running economy (Kaur et al 2017) or cycling economy (Clevidence et al 2012;Kilding et al 2018) have been reported. Furthermore, increasing the number of ischemic episodes during an acute application (up to 8 x 5-min), beyond the traditional 4 x 5-min protocol, elicited no additional improvements in performance (Cocking et al 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the calculated HR slope over the last minute was small (1.4 beats.min -1 ). Besides, even during truly steady state conditions, thus while running below lactate threshold and with longer (5 min) exercise blocks, HR does not completely level off [ 36 ]. Therefore, we believe that HR values and thus the speed range used in this study sufficiently reflect training intensities of this group of runners.…”
Section: Discussionmentioning
confidence: 99%
“…Out of these articles, 7 looked at running exercises. They found no effect during sprints, 44 submaximal running, 45 short distance running, 46 endurance performance in the heat, 47 time trials, 20 maximal acceleration, 48 and running on a field 49 . Four articles found no effect of IPC during cycling performances, such as submaximal cycling, 3 maximum cycling, 21 cycling at high altitude, 50 and anaerobic cycling 25 .…”
Section: Resultsmentioning
confidence: 97%
“…Some of the 52 articles in this systematic review noted that further research should find out more about the effect of IPC on local factors, such as working limb flow, oxygen delivery, arteriovenous oxygen difference, 50 energy cost of endurance events, 45 and changes in intramuscular metabolism 36 . These parameters are often forgotten in analyses.…”
Section: Discussionmentioning
confidence: 99%